An Analysis of Students' Speaking Problems in Online Classroom: How They Communicate During Distance Learning - Reny Valerina Fantasya (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Speaking is a skill that the most individuals be desirous of perfectlyexecuted because students are encouraged to focus on learning English. This study aimed to describe the problems and the factors encountered by EFL students in the fourth semester at University of Islam Malang during online learning for speaking and how they dealed with their problems. The descriptive qualitative method was used in this study. The population in this study is all fourth semester students in speaking class with samples chosen based on the results of the questionnaire considered who had the problems in online speaking class. For a total of six students being interviewed. In this study, questionnaires and interviews were used to collect the data. The findings of this study, it provides information about the problems, factors, and ways to overcome speaking problems in online learning. It is addressed to the English lecturers to give the students new methods on how to speak in other ways. And the students can apply these various strategies to deal with speaking in online class, so they can communicate effectively and fluently.Â Keywords:Â Speaking, problems, online